THE IMPORTANCE OF THE UNIVERSITY FOR THE CITY ECONOMY: AN EXAMPLE OF THE IMPACT OF A DISPLACED UNIVERSITY - NESTORENKO, TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the importance of a displaced university for the economy of the host city. The main directions of the impact of the displaced university on the local economy are analysed. The role of the displaced university for the revenue of the budget of the host city is considered. The example of Donetsk National Technical University shows the importance of displaced university for employment of the local population and reducing the rate of migration. The study aims to determine the impact of displaced universities on the economy of host cities (on the example of Donetsk National Technical University and Pokrovsk city). As a result of moving to the territories controlled by the Ukrainian authorities, the displaced universities, on the one hand, lost a significant part of their assets and found themselves in a difficult situation due to limited resources to continue their core business (training future professionals). On the other hand, the relocation of such universities was the impetus for the further development of host cities. The displaced university provides local youth with the opportunity to obtain higher education without leaving for other cities. Through their activities, displaced universities are creating new jobs for locals. Also, displaced universities are becoming big taxpayers to the local budget. That is why the support of displaced universities by the state and international organizations (granting certain preferences, financial assistance, etc.) will contribute not only to the "survival" of such universities but also to the socio-economic development of host cities. The study found that Donetsk National Technical University as a displaced university has a positive impact on the economy of the city of Pokrovsk: the university uses and pays for utilities provided by local businesses, buys goods and food from local producers. The university pays local taxes and fees to the local budget. Also, the local budget receives the taxes from university staff. Thanks to the activities of the university, about 400 jobs were created in the Pokrovsk city.
Keywords: relocated university; economic impact; direct impact; host city; local budget; students; working places